Estudo do comportamento voltamétrico de nitro-heterocíclicos - Chiavassa, Luisa Donatto [UNIFESP] (2018)
Nitrocompounds exhibit a broad spectrum of biological action and the knowledge of their reduction mechanism can contribute to better understand their biological action. The reduction of nitrofurazone, nitrofurantoin, chloramphenicol, ornidazole and metronidazole was studied by cyclic voltammetry (CV) using a carbon fiber microelectrode as working electrode. The observed behavior demonstrated that the reduction mechanism for all compounds is similar in acidic medium, involving the same number of electrons, having as main product the formation of hydroxylamine derivative. The electrochemical reduction of nitrofurazone (NF), nitrofurantoin (NT) and furazolidone (FZ) was studied by square wave voltammetry (SWV) in aqueous medium. A single cathodic peak in acidic medium was recorded, confirming the same behavior recorded by CV. In the alkaline medium, the original peak was unfolded in two peaks, being the former reversible and pH-independent, corresponding to the nitro radical anion generation confirmed by the electrons number calculation for each compound, and the latter, irreversible and pH-dependent, corresponding to the hydroxylamine formation. The ratio between the direct and reverse current components and the amplitude variation analysis can indicate the existence of an EC mechanism, in which there is a disproportionation reaction after the charge transfer process. From the theoretical models and considering the disproportionation of the product formed, the kinetic constant value could be estimated. The reduction of NF was also studied by CV and SWV in nonaqueous medium using four different ionic liquids (ILs): BMImTf2N, EMImTf2N, BMImBF4 and BMMImTf2N. The NF showed similar reduction behavior in the four ILs, having a single reversible cathodic peak recorded in BMImBF4 and BMImTf2N. On the other hand, in BMMImTf2N and EMImTf2N, two reversible cathodic peaks were recorded. The reversibility of the former could also be observed by CV, since a reversible redox pair was recorded for this reduction. From the frequency variation, the systems reversibility with product and reagent adsorptions on the electrode surface was confirmed. The electrons number calculation involved in this reduction indicated the nitro radical anion formation followed by its respective dianion. For the first reduction, the EC mechanism was also considered for the systems in non-aqueous medium, in which there was a dimerization reaction after the charge transfer process, being the kinetic constants calculated following the Olmstead and Nicholson model.